2015
DOI: 10.1016/j.bjbas.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Study on toxigenic fungi in ruminant feeds under desert conditions with special references to its biological control

Abstract: Saccharomyces Biocontrol Mycotoxins Feedstuff Egypt Aspergillus flavus a b s t r a c t A total of 435 samples from feedstuff (130 samples of commercial ration feed storage from 1e30 days, 77 samples of commercial ration stored higher than 30 days, 57 samples from each of, derris, grind mixture, Tibn and wheat bran) were collected from the feed store houses of private farms located at the desert regions of Ras Sudr at South Sinai and Elameria area at Alexandria Governorate, from December 2012 to May 2014. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
1
0
3
Order By: Relevance
“…It is a well-documented problem in poultry and pigs pellets that are rich in grains [ 12 ]. Similarly, in grain-rich ruminant feeds, Hegazy et al [ 27 ] found fungi, such as Aspergillus flavus , A. niger , Alternaria spp., A. fumigates and A. terreus , Cladosporium spp., Fusarium spp., Mucor spp., Penicillium spp., Trichoderma spp., and Rhizopus spp. In addition, identified fungal strains in grain-rich pellets, stored at different temperatures for 3 months, included Eurotium amstelodami , Scopulariopsis brevicaulis , A. candidus , A. niger , A. unguis , Trichomonascus ciferrii , Stepharoascus ciferrii , Absidia corymbifera , and Rhizopus microspores .…”
Section: Discussionmentioning
confidence: 99%
“…It is a well-documented problem in poultry and pigs pellets that are rich in grains [ 12 ]. Similarly, in grain-rich ruminant feeds, Hegazy et al [ 27 ] found fungi, such as Aspergillus flavus , A. niger , Alternaria spp., A. fumigates and A. terreus , Cladosporium spp., Fusarium spp., Mucor spp., Penicillium spp., Trichoderma spp., and Rhizopus spp. In addition, identified fungal strains in grain-rich pellets, stored at different temperatures for 3 months, included Eurotium amstelodami , Scopulariopsis brevicaulis , A. candidus , A. niger , A. unguis , Trichomonascus ciferrii , Stepharoascus ciferrii , Absidia corymbifera , and Rhizopus microspores .…”
Section: Discussionmentioning
confidence: 99%
“…Zanieczyszczenie pasz grzybami i ich zarodnikami jest częstym tematem doniesień w literaturze światowej (7,30). Według raportu Hegazy i wsp.…”
Section: Drożdże I Pleśnie W Paszyunclassified
“…Według raportu Hegazy i wsp. (30), głównymi grzybami pleśniowymi występującymi w paszach dla przeżuwaczy są: Penicillium spp., Aspergillus flavus, Cladosporium spp., Mucor spp., Trichoderma spp., Aspergillus niger, Alternaria spp., Rhizopus spp., Fusarium spp., A. fumigates i A. terreus. Jak wynika z badań Cegielskiej-Radziejewskiej (7), do najczęstszych rodzajów grzybów pleśniowych wykrywanych w paszach dla drobiu należą: Aspergillus, Rhizopus i Mucor.…”
Section: Drożdże I Pleśnie W Paszyunclassified
See 1 more Smart Citation